Sosialisasi Program Sertifikasi Halal untuk Meningkatkan Kepercayaan Konsumen pada Produk UMKM di Desa Jerukwangi - Anam, M. Khoirul; Alvianti, Refy; Zainuddin, Moch.; Syakur, Ahmad; Khalik, Jamaludin A.; Anam, Choiril; Sariati, Ning Purnama (Welfare : Jurnal Pengabdian Masyarakat, 2023)
This community service aims to increase consumer confidence in MSME products in Jerukwangi Village through socializing the halal certification program. The service method applied is service learning, where service participants play an active role in providing understanding to MSME players about the importance of halal certification. The main objective involves participants in interactive and participatory learning, enabling them to understand firsthand the positive impact of the halal certification program on increasing consumer confidence. The results of the service include a better understanding from MSME players regarding the process of obtaining halal certification, improving product quality, and increasing consumer confidence. Thus, it is hoped that this service can make a positive contribution to the development of MSMEs in Jerukwangi Village through increasing compliance with halal principles and increasing product competitiveness.